1975
DOI: 10.3109/00365597509180918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Antebrachial Cimino-Brescia Arteriovenous Fistula on the Local Circulation in the Hand

Abstract: A female patient with a side-to-side fistula between the radial artery and the cephalic vein complained of pain in the three radial fingers during dialyses. Using 133-Xenon and histamine injected locally into the thumb musculature, local effective arterial pressure was found to be decreased, and to rise after compression of the fistula, or the radial artery distal to the fistula. The patient's symptoms thus were probably ischaemic and disappeared after ligation of the radial artery distal to the fistula. Ten m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…E. Harding and J. le Fanu graphy that a radial-cephalic arteriovenous fistula constantly gives rise to increased forearm blood flow and reduced thumb blood flow. This was confirmed by Lindstedt and Westling (1975). They found that the disappearance of '33Xenon from the adductor pollicis was substantially reduced in patients with antebrachial arteriovenous fistulas.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…E. Harding and J. le Fanu graphy that a radial-cephalic arteriovenous fistula constantly gives rise to increased forearm blood flow and reduced thumb blood flow. This was confirmed by Lindstedt and Westling (1975). They found that the disappearance of '33Xenon from the adductor pollicis was substantially reduced in patients with antebrachial arteriovenous fistulas.…”
Section: Discussionmentioning
confidence: 75%
“…These symptoms were attributed to the carpal tunnel syndrome but this was not confirmed by nerve conduction studies. Lindstedt and Westling (1975) have also reported the occurrence of pain in the radial three fingers of the hand during haemodialysis employing an antebrachial Cimino-Brescia arteriovenous fistula. Warren and Otieno (1975) related the occurrence of symptoms attributed to median nerve dysfunction in their cases to oedema secondary to the increased venous pressure in the hand produced by the fistula.…”
Section: Casementioning
confidence: 94%
“…19,20 The anesthesia literature is replete with reports of digital and hand necrosis following radial artery cannulation, [21][22][23][24][25][26] and general surgical journals report cases of acute ischemia of the hands and digits as a complication of using the radial artery in arteriovenous fistula creation for dialysis access. [27][28][29][30] Avoiding sacrifice of the radial artery has been addressed by the development of a distally based radial artery flap vascularized by distal perforators. 7,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] It has been used both as a fasciocutaneous flap and as an adipofascial flap, either alone or in combination with a full-thickness skin graft for hand wound coverage.…”
mentioning
confidence: 99%
“…It was shown that the Cimino-Brescia fistula caused a marked increase of blood flow in the forearm. Simultaneously, the blood flow and blood pressure in the thumb was reduced by a vascular steal mechanism, and the direction of the flow in the distal part of the radial artery was reversed (135)(136)(137)(138). The symptoms of median nerve dysfunction were accordingly explained by ischaemia.…”
Section: Post Vascular Access Neuropathymentioning
confidence: 97%
“…In four of them diminished tactile sensation in the area innervated by the median nerve, was present immediately after dialysis, disappearing within 24 h. No other abnormalities of motor and sensory functions were found and nerve conduction studies were normal in their patients. Subsequently a number of other dialysis patients with carpal tunnel syndromes, mostly with motor deficit and cutaneous sensory impairment, have been reported (134)(135)(136)(137)(138)(139).…”
Section: Post Vascular Access Neuropathymentioning
confidence: 99%